Easy Access to N-(Pyridin-2-yl)benzamides through Electro-oxidative Ring Opening of 2-Arylimidazo[1,2-a]pyridines - Ghosh, Sayan; Dutta, Jhilik; Halder, Atreyee; De Sarkar, Suman (Synlett, 2022)
An electro-oxidative method for the ring opening of imidazopyridine derivatives is reported. This mild protocol offers a sustainable alternative to the existing harsh reaction conditions and unleashes an efficient approach to produce N-(pyridin-2-yl)amide derivatives with good tolerance of different functional groups. Systematic mechanistic studies provided insight into the reaction pathway and revealed that the residual water of DMSO is the source of oxygen atoms in the products.
Keywords: electrosynthesis; C–C bond cleavage; imidazopyridine; oxidative ring opening; radicals